Cellulose Extraction from Coconut Coir with Alkaline Delignification Process - Aster Rahayu; Farrah Fadhillah Hanum; Nafira Alfi Zaini Amrillah; Lee Wah Lim; Siti Salamah (Journal of Fibers and Polymer Composites, 2022)
Coconut has been known for its benefits in human life. Coconut coir, as part of coconut which is considered as waste, contains useful components. It contains high cellulose which is could be used in fiber industries. Meanwhile, coconut coir also contains lignin which needs to be separated. In this study, a delignification process was used to remove the brown color on the fiber caused by the lignin content. The delignification process was a pretreatment before the cellulose extraction was carried out. It had been done in the various NaOH concentration (0.5; 1; and 1.5 M), reaction time (1; 1.5; and 2 hours) and the reaction temperature (60,70, and 80 oC). This study aims to determine the cellulose content and the factor that affected the cellulose extraction and the characteristics of the cellulose extracted from the coconut coir. The Chesson Data method and SEM analysis have been used for the characterization of the cellulose. The delignification method known has the potential as a simple and effective method for extracting cellulose from natural materials. The result shows that the optimum cellulose content obtained at 100 mesh coir particle size, 1.5 M NaOH concentration, at 80°C for 1.5 hours was 69.82 %.